UMP's pioneer rail technology course to start in September - UMP, PNC (The New Straits Times Press (M) Bhd., 2017)
PEKAN: The pioneering batch of 300 students of Universiti Malaysia Pahang's (UMP) rail technology course will start their studies this September, as part of the ambitious East Coast Rail Link (ECRL) project.